Plasmonic nanosensor based on multiple independently tunable Fano resonances - Cheng, Lin; Wang, Zelong; He, Xiaodong; Cao, Pengfei (Beilstein Journal of Nanotechnology, 2019)
A novel refractive index nanosensor with compound structures is proposed in this paper. It consists of three different kinds of resonators and two stubs which are side-coupled to a metal–dielectric–metal (MDM) waveguide. By utilizing numerical investigation with the finite element method (FEM), the simulation results show that the transmission spectrum of the nanosensor has as many as five sharp Fano resonance peaks. Due to their different resonance mechanisms, each resonance peak can be independently tuned by adjusting the corresponding parameters of the structure. In addition, the sensitivity of the nanosensor is found to be up to 1900 nm/RIU. For practical application, a legitimate combination of various different components, such as T-shaped, ring, and split-ring cavities, has been proposed which dramatically reduces the nanosensor dimensions without sacrificing performance. These design concepts pave the way for the construction of compact on-chip plasmonic structures, which can be widely applied to nanosensors, optical splitters, filters, optical switches, nonlinear photonic and slow-light devices.
Keywords: Fano resonance; metal–dielectric–metal (MDM) waveguide; nanosensor; on-chip plasmonic structures; surface plasmon polaritons (SPPs)